האחריות קודמת לסגפנות: הביקורת של עמנואל לוינס על האונטו-תיאולוגיה - פניוטו סטברוס (מחשבת ישראל, 2021)
In this paper, I explore Emmanuel Levinas’s ethical dialectic on asceticism and its relation to otherness and closeness. In parallel, I argue that Levinas’s stance on asceticism constitutes a vehement criticism of the analytic insistence on onto-theology. In Levinas’s later works, particularly Otherwise than Being or Beyond Essence, he maintains that Christian asceticism (especially in the Orthodox and Protestant traditions) has mistakenly focused on onto theology, i.e., on an incarnated God who comes to mind. On the one hand, a number of continental thinkers argue that an individual can achieve direct communication with God through a symmetrical, reciprocal relation as a self-contained unit. Kierkegaard, for instance, claims that the subject’s isolation through asceticism is a necessary and sufficient condition to meet God. As each person is responsible directly to God and his responsibility is a matter of his faith, the religious life does not coincide with ethics and sometimes even appears as an absurdity if measured by ethical norms. Similarly, Heidegger endorses the radical replacement of religion, prioritizing consciousness and cognition as necessary and sufficient conditions to comprehend God, via the esotericism of Dasein. Levinas raises severe objections to these positions. He claims that God exists outside of the cosmos and that we can seek only His trace through the other person. Hence, an individual cannot be in a direct relation with God as the person is a finite being and God is Transcendence (Infinity). This is why God disappears from human relations after sending the Other to me and subjugating me as a hostage. It is only here that we can speak about asceticism, that is, the individual must appear only as an equal interlocutor, as a subject, not as an object, emptying itself and abandoning all its ontological narcissistic criteria for the Other. In this sense, the ascetic self always starts from the Other. However, Levinas goes further, arguing that God leaves all human affairs in our own hands, absenting Himself almost entirely from our world. To Levinas, the individual is a subject in the sense of being commanded by and thus subject to God. One’s thinking and consciousness is awakened not by exploiting the face of the Other but by serving it eternally as an infinite call and response, as a substitute for a direct relationship with the Divine. One’s self-conscious personality, the “I,” is secondary to the morally subjected “me” which practices asceticism for the sake of the Other.